Sub-Saharan Africa : A Survey of Gender Budgeting Efforts - Stotsky, Janet (IMF Working Papers; Working Paper, 2016)
Gender budgeting is an initiative to use fiscal policy and administration to address gender inequality and women's advancement. A large number of sub-Saharan African countries have adopted gender budgeting. Two countries that have achieved notable success in their efforts are Uganda and Rwanda, both of which have integrated gender-oriented goals into budget policies, programs, and processes in fundamental ways. Other countries have made more limited progress in introducing gender budgeting into their budget-making. Leadership by the ministry of finance is critical for enduring effects, although nongovernmental organizations and parliamentary bodies in sub-Saharan Africa play an essential role in advocating for gender budgeting.